Problems of Management of Technological Systems Under Uncertainty: Models and Algorithms - Jo‘rayev Farrux Do‘stmirzayevich; Aralov G‘ayrat Muhammadiyevich; Eshonqulov Javohir Sobirovich (Global Scientific Publishing, 2023)
It is known that the importance of model management is very high in the management of a technological system under conditions of uncertainty. Model management provides an opportunity to qualitatively manage the system based on quantitative criteria. The article investigates the mechanism of improving the quality of technological system management decisions under conditions of uncertainty. Based on the parametric improvement of control and forecast models, it is proposed to use a new methodical approach to increase the accuracy of the description of the technological object and control system. The effectiveness of adjusting the control object of the system to optimality in improving the quality of management decisions of a technological system of a complex nature under conditions of uncertainty is substantiated. A prototype model of the management object was selected as a research experiment, and the qualitative changes of management based on quantitative changes were considered as the most important criterion according to this model. Improvement of the model theoretically led to the solution of the problem of mathematical programming, expanded the possibilities of practical application. Algorithms of using the mathematical programming method were developed in the improvement of the prototype model. The essence of the parametric improvement of the object model in the qualitative management of an uncertain system with a control object is revealed on the basis of the law of quantitative changes leading to qualitative changes. A new approach to improving the mechanism for increasing the quality of decision-making in the optimal management of uncertain systems is proposed.
Keywords: Fuzzy system; control object; model; mathematical programming